Establishing the basis for a school bus emergency evacuation time standard. (June 2021) - Davis, Gerard A.; Abulhassan, Yousif
Highlights: Potential issues of current school bus emergency evacuation systems are discussed. Comparison of airplane evacuation criteria to school bus evacuation criteria. Need for a systems approach to propose an emergency evacuation time standard. Abstract: Though it is commonly accepted that transporting children by school bus is the safest way to move them to and from school, the frequency of events causing full or partial evacuations each year is relatively unknown. As research demonstrates that the interior of a bus can be completely burned-out in as few as three minutes, it raises the question as to why there is not a federal school bus evacuation time standard in place. The objective of this paper was to present the need of a school bus evacuation time standard that can enhance post-accident school bus passenger safety. Passenger train and commercial aircraft evacuation standards were studied to identify how school bus evacuation standards compare to those of other modes of mass transportation. Considerations for the proposal of an evacuation time standard while focusing on the unique challenges associated with school buses are discussed.